McDowell on Transcendental Arguments, Scepticism and “Error Theory” - Thomas, Alan (International journal for the study of skepticism, 2014)
John McDowell has recently changed his line of response to philosophical scepticism about the external world. He now claims to be in a position to use the strategy of transcendental argumentation in order to show the falsity of the sceptic’s misrepresentation of our ordinary epistemic standpoint. Since this transcendental argument begins from a weak and widely shared assumption shared with the sceptic herself the falsity of external world scepticism is now demonstrable even to her. Building on the account of perceptual intentionality defended in the Woodbridge lectures, McDowell argues that the idea of narrow perceptual content is unavailable to anyone, including the sceptic. This argument is assessed by drawing out an analogy with parallel responses to error theories in ethics.